Nurse–Patient/Relatives Conflict and Patient Safety Competence Among Nurses - Abdualrahman Saeed Alshehry PhD, RN (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2022)
Nurse–patient/relatives conflicts may adversely impact the well-being and work performance of nurses, which could prelude to the possibility of unwanted errors thereby threatening patient safety. This descriptive and cross-sectional study aimed to examine the association between nurses’ perceived nurse–patient/family conflicts and their perceived patient safety (PS) competence. Nurse–patient/relatives conflicts are critical issues that may adversely impact the nurses’ well-being, which could prelude to unwanted errors, thereby threatening PS. The study surveyed 320 nurses in Saudi Arabia using the “Healthcare Conflict Scale” and “Health Professional Education in Patient Safety Survey” from December 2019 to January 2020. The subscale “mistrust of motivations” was perceived to have the greatest conflict, whereas “contradictory communication” was rated as the lowest conflict. A significant difference was observed between the perceived conflict and the different hospital units where nurses worked. Saudi nurses reported higher nurse–patient/family conflicts than Filipino and Indian nurses. The highest PS competence was reported in “communicating effectively,” whereas “working in teams with other health professionals” had the poorest safety competence. The nurses’ perceived “mistrust of motivations” and “contradictory communication” were associated with poorer self-reported PS competence. Perceived conflicts between nurses and their patients/relatives had negative association with the perceived confidence of nurses in the difference patient safety competencies. The results can become the basis for formulating hospital policies geared toward the elimination of healthcare conflicts to help ensure the patient safety competence of nurses. Policies on mitigating conflicts between healthcare workers and patients/relatives must be created and implemented.